If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 + 12x = 61 + 8x Solving -39 + 12x = 61 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -39 + 12x + -8x = 61 + 8x + -8x Combine like terms: 12x + -8x = 4x -39 + 4x = 61 + 8x + -8x Combine like terms: 8x + -8x = 0 -39 + 4x = 61 + 0 -39 + 4x = 61 Add '39' to each side of the equation. -39 + 39 + 4x = 61 + 39 Combine like terms: -39 + 39 = 0 0 + 4x = 61 + 39 4x = 61 + 39 Combine like terms: 61 + 39 = 100 4x = 100 Divide each side by '4'. x = 25 Simplifying x = 25
| 6=z/9.2 | | t/3=-21 | | y=1.6+9.5 | | -1.554878048878=n/16.4 | | -0.5(9.81)t^2+45=0 | | 4x-9=6x+12 | | -6(7m+8)-m=40+m | | 12k=-48 | | -0.5(4.905)t^2+45=0 | | ln(4x+3)-ln(2x-5)=0 | | 30=x+(2x-2)+(x-4) | | 3.4X-8=32.2 | | -x-72=96-9x | | X^2+4x+4=4+x^2 | | 7x+6(4x-22)=240 | | 9z+2=5y | | -13=5-x | | 10k-8=8k+10 | | 2r-2=8 | | 4x-2+y=-2x | | 12.5(72)= | | 2x+9x-60=83 | | 5y=9z+2 | | 72=12x-3x | | 3z=z+14 | | 4+6(1+4n)=130 | | -7m-3=-24 | | (2.5x)+(3.5x)= | | 10b^2+5=-167 | | x-1+121=180 | | -6x+6=6+5x | | 4+6(1+4)=130 |